2020
DOI: 10.1371/journal.pone.0238077
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter study of the prevalence and risk factors of malaria and anemia among pregnant women at first antenatal care visit in Ghana

Abstract: Background Malaria in pregnancy remains a major public health problem in Africa and Ghana and has been associated with a variety of pregnancy-related adverse complications. The development of effective and timely health policies for the prevention and control of malaria and anemia in pregnancy; requires current and consistent data on the prevalence and risk factors. We report the prevalence and risk factors of malaria and anemia from three major hospitals across three regions in Ghana. Methods This multicenter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
41
4
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 44 publications
9
41
4
2
Order By: Relevance
“…No difference in parasite prevalence by gravidity was observed, which differs from other studies, which found higher prevalence in primi- and secundigravidae, compared to multigravidae [ 32 , 33 ]. This may be because in our study setting pregnant women are, irrespective of gravidity, exposed to same high level of transmission, and hence the probability of getting infected is quite similar.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…No difference in parasite prevalence by gravidity was observed, which differs from other studies, which found higher prevalence in primi- and secundigravidae, compared to multigravidae [ 32 , 33 ]. This may be because in our study setting pregnant women are, irrespective of gravidity, exposed to same high level of transmission, and hence the probability of getting infected is quite similar.…”
Section: Discussioncontrasting
confidence: 99%
“…The finding that literate women had 2.54 times the odds of P. falciparum infection compared to illiterate women was unexpected. While literature on this is mixed, with some studies showing an association between literacy and reduced infection [ 32 ] and others showing no such association [ 33 , 37 ], to the best of our knowledge there are no other studies which found a higher odds of infection in literate women. There was no association between literacy and ITN use, ANC attendance or IPTp-SP doses, suggesting that literacy is not acting via reduced uptake of preventive measures.…”
Section: Discussionmentioning
confidence: 96%
“…In line with the results of research conducted by Fondjo (2020), among pregnant women with anemia, among them suffer from malaria. Regression analysis of the studies revealed that malaria increased the risk of anemia by up to twofold among the population.…”
Section: Discussionsupporting
confidence: 79%
“…Comparatively, between 2011 and 2019, the prevalence reduced and has ranged between 10 and 17% [ 27 32 ] though much lower measures of 3.5–5.5% continue to be recorded in urban and peri-urban areas of Accra [ 33 , 34 ]. In spite of these relatively lower prevalence recorded for peripheral blood films over the period, polymerase chain reaction (PCR) evaluations showed comparable or much higher prevalence of up to 43% and 12.6% for peripheral and placental parasitaemia, respectively over 2015–2017 [ 34 ].…”
Section: Resultsmentioning
confidence: 99%